Advanced brain aging mediates the relationship between cardiovascular health and aphasia severity in chronic stroke - Natalie Busby; Ida Rangus; Nicholas Riccardi; Roger Newman-Norlund; Chris Rorden; Julius Fridriksson; Leonardo Bonilha (Aging Brain)
Introduction: There is evidence that overall physical health in general and cardiovascular risk (CV) factors in particular are associated with structural brain changes and recovery trajectories in stroke aphasia, however the nature of these relationships is still unclear. Therefore, we investigated the mediating role of advanced brain aging on the relationship between cardiovascular health and aphasia severity in chronic stroke. Methods: Participants (N = 95) with chronic stroke aphasia completed behavioral testing including the Western Aphasia Battery Aphasia Quotient (WAB AQ) and MRI scanning. Brain age of each participant was calculated using BrainAgeR and their proportional brain age (PBA) was calculated through the relative difference between estimated brain age and chronological age. A CV risk score was also calculated for each participant using the Framingham Heart Study General Cardiovascular Disease Risk Prediction Using BMI calculator. To determine if the relationship between vascular score and WAB AQ is related to brain age, we performed a statistical mediation analysis where the independent variable was vascular score, the dependent variable was WAB AQ and the mediating variable was PBA. Results: Individuals with chronic stroke aphasia who had more cardiovascular risk factors (i.e., a higher vascular score), typically had worse aphasia severity (lower WAB AQ) and advanced brain aging (increased PBA). An increased PBA was also associated with worse aphasia severity. Mediation analyses revealed that individuals with a higher vascular score (i.e., worse heart health) typically had advanced brain aging and, in turn, advanced brain aging was associated with worse aphasia severity. Therefore, the total effect of cardiovascular health on aphasia severity is partially explained by the indirect effects of advanced brain aging. Discussion: Our results corroborate the previous findings suggesting that physical health is an important factor for both brain structural integrity and recovery in stroke aphasia and extends this by demonstrating the mediating effect of advanced brain aging on the relationship between cardiovascular health and aphasia severity. These results highlight the importance of maintaining physical health alongside aphasia therapy and may be an important factor to consider in the long-term management of chronic stroke. Ensuring that individuals have access to resources needed for proper exercise and maintaining a balanced diet may help to improve overall brain structural integrity and therefore may impact aphasia severity.